A Dynamic Behavior of Hyperglycemia Model Based on Reaction-Diffusion Cellular Nonlinear Networks (RDCNN). Issue 17 (2021) - Ali, Ahmed M. Ali; Tahir, Fadhil R.; Al-Suhail, Ghaida A.; Abbood, Hamzah Abdulkareem
Abstract: Diabetes Mellitus (DM) is a disorder resulting from a malfunction in the glucose-insulin interaction dynamic inside the human body. To model such pathophysiology (DM), we suggest a new mathematical model for the insulin-glucose regulation system is introduced based on the well-known Lokta-Volterra model. The proposed system is then converted using RD-CNN for introducing 3D forms presenting such system behavior as unpredictable pattern formation. To further studies, as all the system parameters can be controllable, one can consider the efficiency of newly proposed drugs by considering the relevant parameter in this model. This paper's overall result may help a better understanding of the diabetes mellitus regulation system, including diseases such as Hyperglcymia related to the polycystic ovary (PCOS) based RD-CNN which is called the pre-diabetes disease of Type2 DM.